Carbon Composite Materials

The carbon composite member with pyrolytic carbon pores at the interface addresses peeling issues by reducing thermal expansion coefficient differences, ensuring durability and contamination prevention under heat cycles.

JP7613829B2Active Publication Date: 2025-01-15IBIDEN CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2019135431
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-07-23
Publication Date
2025-01-15
Estimated Expiration
2039-07-23

AI Technical Summary

Technical Problem

Existing carbon composite members with pyrolytic carbon coatings on graphite bases experience peeling due to thermal expansion coefficient differences when subjected to intense heat cycles, leading to thermal distortion and stress.

Method used

A carbon composite member with a pyrolytic carbon layer having pores near the interface with the graphite base material, where the pores disturb the crystal orientation, reducing the thermal expansion coefficient difference and enhancing adhesion.

Benefits of technology

The pyrolytic carbon layer is less likely to peel off from the graphite base material even under large temperature variations, maintaining structural integrity and preventing contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613829000001
    Figure 0007613829000001
  • Figure 0007613829000002
    Figure 0007613829000002
  • Figure 0007613829000003
    Figure 0007613829000003
Patent Text Reader

Abstract

To provide a carbon composite material having a pyrolytic carbon layer formed on a graphite base material, the graphite base material being less likely to peel off even if a heat cycle having a large temperature difference is applied thereon.SOLUTION: A carbon composite material 1 has a pyrolytic carbon layer 3 formed on a graphite base material 2, wherein the pyrolytic carbon layer 3 has pores 4 near a boundary surface between the pyrolytic carbon layer 3 and the graphite base material 2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon composite component. [Background technology]

[0002] Carbon materials such as graphite are used in many fields, including semiconductor manufacturing, chemical industry, machinery, and atomic energy, due to their excellent chemical stability, heat resistance, and mechanical properties. In addition, graphite itself is porous, and therefore gas, moisture, impurities, and the like are easily adsorbed inside the pores, making the inside of the pores susceptible to contamination. For this reason, a technology is known for reducing the adverse effects of graphite by applying a pyrolytic carbon coating to prevent these contaminants from being re-released from the pores.

[0003] However, since the thermal expansion coefficients of the pyrolytic carbon coating layer and graphite are different, thermal distortion and stress are likely to occur at the interface between the two when exposed to heat. -6 / ℃~6.0×10 -6 A graphite electrode for electrochemical machining has been proposed, which has a graphite base material with a thermal conductivity of 100 / °C and a pyrolytic carbon coating on its surface. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 5-285735 Summary of the Invention [Problem to be solved by the invention]

[0005] The graphite electrode for electrochemical machining described in Patent Document 1 is intended to be used in a substantially constant temperature environment. However, in the above-mentioned applications such as semiconductor manufacturing, repeated heating and cooling are performed, so that a severe heat cycle is applied between the graphite base material and the pyrolytic carbon layer. Therefore, the electrode is exposed to an even more severe environment for peeling.

[0006] In view of the above problems, an object of the present invention is to provide a carbon composite member in which a pyrolytic carbon layer is formed on a graphite base material, and in which the pyrolytic carbon layer is unlikely to peel off even when a heat cycle with a large temperature difference is applied. [Means for solving the problem]

[0007] The carbon composite member according to the present invention for solving the above problems is as follows.

[0008] (1) A carbon composite member having a pyrolytic carbon layer formed on a graphite substrate, A carbon composite member, wherein the pyrolytic carbon layer has a region in which pores exist near the interface between the pyrolytic carbon layer and the graphite base material.

[0009] In the carbon composite member according to the present invention, the pyrolytic carbon layer has a region in which pores exist near the interface between the pyrolytic carbon layer and the graphite substrate, and thus the crystal orientation of the pyrolytic carbon is disturbed around the pores. As a result, the thermal expansion coefficient in the planar direction of the pyrolytic carbon layer is influenced by the thermal expansion coefficient in the c-axis direction of the pyrolytic carbon layer, which acts to increase the thermal expansion coefficient, thereby reducing the difference in the thermal expansion coefficient near the interface between the pyrolytic carbon layer and the graphite substrate. As a result, even if a heat cycle with a large temperature difference is applied, peeling of the pyrolytic carbon layer from the graphite substrate can be suppressed.

[0010] The carbon composite member according to the present invention preferably has any of the following aspects (2) to (6).

[0011] (2) The pores are concentrated in the vicinity of the interface.

[0012] Since the pores are concentrated in the vicinity of the interface between the pyrolytic carbon layer and the graphite base material, the difference in thermal expansion coefficient in the vicinity of the interface can be mitigated, while the gas impermeability of pyrolytic carbon can be sufficiently secured in the portion of the pyrolytic carbon layer away from the graphite base material, thereby preventing contamination of the carbon composite member.

[0013] (3) The pores have a maximum pore size of 0.5 to 3.0 μm.

[0014] By making the maximum pore size of the pores 0.5 μm or more, it is possible to secure a sufficient amount of pyrolytic carbon components with different orientation directions formed around the pores, and the effect of reducing the difference in thermal expansion coefficient between the graphite substrate and the pyrolytic carbon layer by the generation of pores can be fully exerted. Also, by making the maximum pore size of the pores 3.0 μm or less, it is possible to reduce stress concentration around the pores and prevent a decrease in strength due to the presence of the pores.

[0015] (4) When viewed in a cross-sectional view along a stacking direction of the graphite base material and the pyrolytic carbon layer, The maximum pore size is 30% or less of the maximum height difference between the top and bottom of the graphite substrate in a 50 μm section.

[0016] If the pores in the pyrolytic carbon layer are aligned in a row, the pyrolytic carbon layer will be easily peeled off from the graphite base material. However, if the maximum pore diameter satisfies the above condition, appropriate undulations are provided on the surface of the graphite base material, and pores are formed so as not to be aligned in a row along the undulations on the surface of the graphite base material, so that a pyrolytic carbon layer that is not easily peeled off can be obtained.

[0017] (5) The pyrolytic carbon layer has a thickness of 5 to 200 μm.

[0018] By making the thickness of the pyrolytic carbon layer 5 μm or more, the irregularities of the porous graphite base material can be sufficiently covered, and gas impermeability can be ensured. Also, by making the thickness of the pyrolytic carbon layer 200 μm or less, warping and peeling due to thermal distortion of the graphite base material and the pyrolytic carbon layer can be prevented.

[0019] (6) The graphite substrate is an isotropic graphite material.

[0020] Isotropic graphite has small anisotropy in its properties and is highly uniform, so the difference in thermal expansion coefficient between it and the pyrolytic carbon layer is small depending on the location and direction, making it difficult for the graphite to peel off. Effect of the Invention

[0021] In the carbon composite member according to the present invention, the pyrolytic carbon layer has a region in which pores exist near the interface between the pyrolytic carbon layer and the graphite substrate, and thus the crystal orientation of the pyrolytic carbon is disturbed around the pores. As a result, the thermal expansion coefficient in the planar direction of the pyrolytic carbon layer is influenced by the thermal expansion coefficient in the c-axis direction of the pyrolytic carbon layer, which acts to increase the thermal expansion coefficient, thereby reducing the difference in the thermal expansion coefficient near the interface between the pyrolytic carbon layer and the graphite substrate. As a result, even if a heat cycle with a large temperature difference is applied, peeling of the pyrolytic carbon layer from the graphite substrate can be suppressed. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a schematic cross-sectional view of a carbon composite member according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram for illustrating the relationship between the maximum height difference between the top and bottom of the graphite base material and the maximum pore diameter of the pores in a cross-sectional view taken along the stacking direction of the graphite base material and the pyrolytic carbon layer. [Diagram 3] FIG. 3 is a schematic diagram for explaining a method for producing a carbon composite member according to an embodiment of the present invention. [Figure 4] FIG. 4 is a polarizing microscope photograph of a cross section of the carbon composite member obtained in Example 1. [Diagram 5] FIG. 5 is a schematic diagram illustrating FIG. [Figure 6] FIG. 6 is a polarizing microscope photograph of a cross section of the carbon composite member obtained in Comparative Example 1.

[0023] Detailed Description of the Invention 1, a carbon composite member 1 according to this embodiment has a pyrolytic carbon layer 3 formed on a graphite substrate 2, and the pyrolytic carbon layer 3 has a region in which pores 4 exist near the interface between the pyrolytic carbon layer 3 and the graphite substrate 2. In the region in which the pores 4 exist, a plurality of pores 4 having non-uniform pore diameters exist randomly.

[0024] Pyrolytic carbon has the characteristic of being highly anisotropic, with hexagonal mesh planes extending in the plane direction. In addition, pyrolytic carbon is oriented in the a-axis direction of the hexagonal crystals of the graphite structure in the plane direction and in the c-axis direction in the thickness direction, making it a material with high anisotropy in both strength and thermal expansion. The thermal expansion coefficient in the plane direction is 1.7×10 -6 / ℃, 2.7×10 in thickness direction -5 / °C (both average values), which shows a very large anisotropy. In terms of strength, the hexagonal mesh faces are strongly bonded in the plane direction, while in the thickness direction they are only connected by Van Der Waals bonds, so the strength is significantly inferior to that in the plane direction.

[0025] On the other hand, the graphite used as the graphite substrate 2 has a thermal expansion coefficient of 3 to 6 × 10 -6 / °C, which is larger than the thermal expansion coefficient in the plane direction of the pyrolytic carbon layer 3 formed thereon. Therefore, thermal distortion is likely to occur between the graphite substrate 2 and the pyrolytic carbon layer 3, and delamination is likely to occur due to the difference in thermal expansion.

[0026] Therefore, in the carbon composite member 1 according to this embodiment, a region in which pores 4 exist is provided in the pyrolytic carbon layer 3 near the interface with the graphite substrate 2, whereby the crystal orientation of pyrolytic carbon is disturbed around the pores 4, which acts to alleviate the anisotropy of the thermal expansion coefficient and strength. Accordingly, in the plane direction of the pyrolytic carbon layer 3, the thermal expansion coefficient is affected by the thermal expansion coefficient in the c-axis direction, which acts to increase the thermal expansion coefficient, and in the thickness direction of the pyrolytic carbon layer 3, the strength is increased by the strength in the a-axis direction of the hexagonal crystals of the graphite structure. Therefore, even if a pyrolytic carbon layer 3 that originally has a small thermal expansion coefficient in the plane direction is formed on a graphite substrate 2 that has a large thermal expansion coefficient, delamination can be prevented from occurring.

[0027] The pores 4 are preferably unevenly distributed in the vicinity of the interface between the pyrolytic carbon layer 3 and the graphite substrate 2. By unevenly distributing the pores 4 in the vicinity of the interface between the pyrolytic carbon layer 3 and the graphite substrate 2, the difference in thermal expansion coefficient in the vicinity of the interface can be mitigated, while the gas impermeability of pyrolytic carbon can be sufficiently ensured in the portion of the pyrolytic carbon layer 3 away from the graphite substrate 2, and contamination from the carbon composite member 1 can be prevented.

[0028] In this embodiment, the term "vicinity of the interface" refers to a region from the interface between the pyrolytic carbon layer 3 and the graphite substrate 2 to 25% of the thickness of the pyrolytic carbon layer.

[0029] The maximum pore diameter of the pores 4 is preferably 0.5 to 3.0 μm. When the maximum pore diameter of the pores 4 is 3.0 μm or less, stress concentration around the pores 4 can be reduced, and a decrease in strength due to the presence of the pores 4 can be prevented. On the other hand, when the maximum diameter of the pores 4 is 0.5 μm or more, pyrolytic carbon components with different orientations formed around the pores 4 can be sufficiently secured, and the effect of reducing the difference in thermal expansion coefficient between the graphite substrate 2 and the pyrolytic carbon layer 3 due to the formation of the pores 4 can be fully exerted.

[0030] Therefore, by making the maximum diameter of the pores 4 0.5 to 3.0 μm, the difference in thermal expansion coefficient between the pyrolytic carbon layer 3 and the graphite substrate 2 due to the presence of the pores 4 can be reduced, and stress concentration around the pores 4 can be reduced, thereby preventing a decrease in strength due to the presence of the pores 4. In order to more effectively exert these effects, the maximum pore diameter of the pores 4 is more preferably 0.8 to 2.5 μm, and even more preferably 1.0 to 2.0 μm. The size of the pores 4 can be determined by observation with an electron microscope, and the cross-sectional dimensions of the largest pore 4 in the observation field are measured. Pores of irregular shape are confirmed in the longest direction.

[0031] 2, the maximum pore diameter is preferably 30% or less of the maximum height difference ΔH between the top and bottom of the graphite substrate 2 in a 50 μm section in a cross-sectional view along the lamination direction of the graphite substrate 2 and the pyrolytic carbon layer 3. If the pores 4 in the pyrolytic carbon layer 3 are aligned in a row, the pyrolytic carbon layer 3 will be easily peeled off from the graphite substrate 2. However, if the maximum pore diameter satisfies the above condition, appropriate undulations are provided on the surface of the graphite substrate 2, and the pores 4 are formed so as not to be aligned in a row along the undulations on the surface of the graphite substrate 2, so that a pyrolytic carbon layer 3 that is not easily peeled off can be obtained.

[0032] If the maximum pore size with respect to the above ΔH exceeds 30%, the pores 4 become too large, and the pyrolytic carbon layer 3 becomes prone to peeling. The maximum pore size with respect to the above ΔH is more preferably 25% or less, and even more preferably 20% or less. In order to provide a predetermined height difference on the surface of the graphite base material 2, for example, it is possible to appropriately roughen the graphite base material 2 to a predetermined roughness.

[0033] The thickness of the pyrolytic carbon layer 3 is preferably 5 to 200 μm. When the thickness of the pyrolytic carbon layer 3 is 5 μm or more, the unevenness of the porous graphite substrate 2 can be sufficiently covered, and gas, moisture, impurities, etc. are less likely to be adsorbed inside the pores, thereby ensuring impermeability to these gases and impurities. On the other hand, when the thickness of the pyrolytic carbon layer 3 is 200 μm or less, warping and peeling due to thermal distortion of the pyrolytic carbon layer 3 can be prevented. In order to more effectively exert these effects, the thickness of the pyrolytic carbon layer 3 is more preferably 10 to 100 μm, and further preferably 20 to 50 μm.

[0034] The thickness of the pyrolytic carbon layer 3 can be measured by comparing with a standard scale using a polarizing microscope, a scanning electron microscope, etc. When a standard scale is already displayed on the scanning electron microscope or the like, the thickness can be calculated using the scale.

[0035] The graphite base material 2 in the carbon composite member 1 according to this embodiment is preferably an isotropic graphite material. Since isotropic graphite has small anisotropy and high uniformity in properties, the difference in thermal expansion coefficient between the isotropic graphite base material 2 and the pyrolytic carbon layer 3 varies little depending on the location and direction, making it difficult to peel off.

[0036] Next, the carbon composite material 1 according to this embodiment can be obtained, for example, as follows: Figure 3 is a schematic diagram for explaining the process.

[0037] First, a graphite substrate 2 having a desired shape is prepared (FIG. 3(a)). When the pyrolytic carbon layer 3 is formed on the graphite substrate 2, the substrate becomes larger by the thickness thereof. Therefore, it is preferable to process the substrate to be thin according to the size of the carbon composite member 1 and the thickness of the pyrolytic carbon layer 3 to be formed. The surface of the graphite substrate 2 may be roughened in order to improve adhesion with the pyrolytic carbon layer 3 and to make the maximum pore size relative to the above ΔH 30% or less.

[0038] The graphite substrate 2 is placed in a CVD furnace, and the temperature is raised to a film formation temperature, after which a source gas is introduced. The film formation temperature is not particularly limited, but may be, for example, 800 to 2000° C. The source gas for obtaining the pyrolytic carbon layer 3 is not particularly limited as long as it is a hydrocarbon. For example, source gases such as alkanes, such as methane, ethane, propane, and butane, alkenes, such as ethylene and propylene, and alkynes, such as acetylene, as well as aromatic source gases, such as benzene and toluene, may be used. Then, the film-forming temperature is maintained and the raw material gas is introduced for a certain period of time to form a very thin pyrolytic carbon layer 3 on the surface of the graphite substrate 2 (FIG. 3(b)). Note that an inert gas such as Ar can be used as the carrier gas. Note that this very thin pyrolytic carbon layer is optional and does not necessarily have to be formed.

[0039] Next, when the pyrolytic carbon layer 3 has reached a very thin, predetermined thickness, pyrolytic carbon clusters are generated on the surface of the pyrolytic carbon layer 3. The pyrolytic carbon clusters are generated when pyrolytic carbon particles (fine lumps) generated in the air settle and accumulate (i.e., deposit) on the surface of the very thin pyrolytic carbon layer 3.

[0040] The method for generating these clusters is not particularly limited, but for example, the pressure in the CVD furnace may be increased, the temperature may be increased, or the partial pressure of the hydrocarbons may be increased, temporarily throwing off the balance of the pyrolysis reaction and promoting pyrolysis, generating pyrolytic carbon particles in the air, which are then deposited, thereby forming multiple pyrolytic carbon clusters on the surface of the very thin pyrolytic carbon layer 3.

[0041] Moreover, the pyrolytic carbon particles are not only generated in the space above the pyrolytic carbon layer 3, but also grow after falling onto the surface of the pyrolytic carbon layer 3, so that the pyrolytic carbon particles are deposited on the surface of the pyrolytic carbon layer 3 and are integrated with the pyrolytic carbon layer 3. That is, the pyrolytic carbon layer 3 and the pyrolytic carbon clusters formed on its surface are integrated with each other.

[0042] The pyrolytic carbon layer 3 thus obtained, to which the particles are attached, forms pores 4 in the gaps between the clusters, and the crystal orientation of the pyrolytic carbon around the pores 4 is disturbed (FIG. 3(c)). In FIG. 3(c), the randomly oriented short straight lines shown around the pores 4 are a schematic representation of the state in which the crystal orientation of the pyrolytic carbon is disturbed. The size of the resulting pores 4 is approximately the same as the size of the particles.

[0043] An example of the conditions for generating and depositing these pyrolytic carbon particles is a pressure of 10 to 10,000 Pa and a temperature of 800 to 2,000° C. within the CVD furnace.

[0044] Furthermore, in order to deposit more pyrolytic carbon particles on the surface of the pyrolytic carbon layer 3 and form more pores 4, the upper space of the pyrolytic carbon layer 3 in the CVD furnace is made larger. If the upper space is larger, a larger amount of pyrolytic carbon particles are generated, and more pyrolytic carbon particles can be deposited on the surface of the pyrolytic carbon layer 3 and integrated.

[0045] In addition, by applying an electric charge to the graphite substrate 2 or by inverting the graphite substrate 2 in a CVD furnace, it is possible to form pores in the pyrolytic carbon layer 3 not only on the upper surface of the pyrolytic carbon layer 3 but also on the side and lower surfaces of the graphite substrate 2.

[0046] Next, after the pyrolytic carbon particles have accumulated to a certain extent, the pyrolytic carbon is kept constant under the CVD conditions for film formation, and a further pyrolytic carbon layer 3 is formed continuously on the pyrolytic carbon layer 3 in which pores 4 have been formed (FIG. 3(d)).

[0047] Since the pyrolytic carbon layer 3 in which pyrolytic carbon particles are generated and pores 4 are formed, and the pyrolytic carbon layer 3 in which pyrolytic carbon particles are not generated and pores 4 are not formed are successively formed, it is possible to form a pyrolytic carbon layer 3 in which peeling between layers is unlikely to occur. It is preferable that the pyrolytic carbon layer 3 after the particles and pores 4 are simultaneously formed is formed under constant conditions without changing the pressure or temperature in the CVD furnace so as to prevent particles from being generated. In this way, the film is formed without generating particles, and a pyrolytic carbon layer 3 of a predetermined thickness is formed, thereby obtaining a desired carbon composite member 1.

[0048] (Mode for carrying out the invention) The carbon composite member according to the present invention will be further described below with reference to examples and comparative examples so as to clarify the characteristics of the carbon composite member according to the present invention.

[0049] Example 1 The isotropic graphite material was processed to a size of 50 x 50 x 5 mm to prepare a graphite substrate. The obtained graphite substrate was placed in a CVD furnace and heated to 1200°C or higher while reducing the pressure with a vacuum pump. A source gas consisting of hydrocarbons was supplied at a constant partial pressure from the beginning so that the gas pressure in the CVD furnace was 1 kPa or less, and the formation of the pyrolytic carbon layer was started. During film formation, the hydrocarbon gas was continuously consumed, and in a steady state, the partial pressure of the hydrocarbon gas in the furnace was lower than that in the supplied gas. For this reason, if the partial pressure of the hydrocarbon gas is maintained constant from the time of film formation, the partial pressure of the hydrocarbon gas is high in the early stage of film formation, which is thought to facilitate the formation of clusters that form pores on the surface of the graphite base material. Next, when the time came for the pyrolytic carbon layer to grow to a thickness of 20 μm, the supply of the source gas was stopped.

[0050] The cross section of the carbon composite member thus obtained was observed under a polarizing microscope. The polarizing microscope photograph is shown in Fig. 4, and a schematic diagram of the polarizing microscope photograph of Fig. 4 is shown in Fig. 5. In Fig. 5, pores are formed in the vicinity of the interface between the pyrolytic carbon layer and the graphite substrate. The maximum pore diameter observed in Figs. 4 and 5 for Example 1 was 1.05 μm. In addition, in a cross-sectional view along the stacking direction of the graphite substrate and the pyrolytic carbon layer, the maximum pore size was 19% of the maximum height difference between the top and bottom of the graphite substrate in a 50 μm section, and the maximum height difference between the top and bottom of the graphite substrate was 5.5 μm (broken line portion in FIG. 5).

[0051] It was confirmed that this carbon composite member is a functionally gradient material in which the crystal orientation is aligned from the interface with the graphite substrate toward the surface near the interface due to the presence of pores in the pyrolytic carbon layer.

[0052] Comparative Example 1 A carbon composite member was formed in the same manner as in Example 1. However, the ratio of the hydrocarbon gas was initially reduced, and the flow rate of the hydrocarbon gas was gradually increased, and then film formation was performed at a constant partial pressure ratio of the raw material gas in the same manner as in Example 1.

[0053] When the cross section of the carbon composite member thus obtained was observed under a polarizing microscope, it was found that no pores were formed near the interface between the pyrolytic carbon layer and the graphite substrate, and that the pyrolytic carbon layer had a uniform coating direction from near the interface with the graphite substrate to the surface (see Figure 6).

[0054] The present invention is not limited to the above-described embodiment, and can be appropriately modified, improved, etc. In addition, the material, shape, size, numerical value, form, number, arrangement location, etc. of each component in the above-described embodiment are arbitrary as long as the present invention can be achieved, and are not limited. [Industrial Applicability]

[0055] In the carbon composite member according to the present invention, the pyrolytic carbon layer has a region where pores are present near the interface between the pyrolytic carbon layer and the graphite base material, which reduces the difference in thermal expansion coefficient near the interface between the pyrolytic carbon layer and the graphite base material. This makes the pyrolytic carbon layer less likely to peel off even when subjected to a heat cycle with a large temperature difference, and the carbon composite member according to the present invention is useful in many fields, such as semiconductor manufacturing, chemical industry, machinery, and atomic energy. [Explanation of symbols]

[0056] 1 Carbon composite materials 2. Graphite substrate 3 Pyrolytic carbon layer 4. Stoma

Claims

1. A carbon composite member having a pyrolytic carbon layer formed on a graphite substrate, A carbon composite member comprising: a pyrolytic carbon layer having a region in which pores are present near an interface between the pyrolytic carbon layer and the graphite base material; and the pores being unevenly distributed in the vicinity of the interface.

2. The carbon composite member according to claim 1, wherein the pyrolytic carbon layer has a thickness of 5 to 200 μm.

3. 3. The carbon composite member according to claim 1, wherein the graphite substrate is an isotropic graphite material.

Citation Information

Patent Citations

  • Graphite electrode for electro-chemical machining

    JP1993285735A

  • Graphite jig

    JP1994166568A

  • Carbon composite member

    JP2005320208A

  • Muffle, firing furnace, manufacturing method of muffle

    JP2016038191A